(untitled) (The Pakistan Development Review, 2015)
ighly acclaimed and endorsed by leading econometricians, the book “New Directions in Econometric Practice” is not new among the econometrics and statisticians. It is more of a textbook for students of econometrics and statistics at various levels.It impressively attempts to addressthe main objective of explaining ‘how to practice econometrics’. It provides an accessibleand user-friendly approach to a new approach and methodology presented by David Hendry in his book,‘Dynamic Econometrics’. The book under review provides a practical and hands-on illustration ofHendry’s approach, enabling students to use it for themselves inreal world time-series econometric problems. The second edition of thebook attempts to address the shortfalls identified by some reviewers in the first edition. By providing practical guidelines in terms of empirical illustration of each technique,using DHSY’s suggested aggregated timeseries consumption function on PC-Gives (8.1 Professional), it opens new trails ofresearch. The book is primarily designed for providing an intuitive understanding of recent developments in econometrics to nonspecialist econometricians and is widely adopted by teachers, students and practitioners alike